2017
DOI: 10.5194/jsss-6-211-2017
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of certain flight parameters based on MEMS sensors

Abstract: Abstract. Gyroscopes established one of the fundamental references for attitude and heading in aerospace applications. The information about angular velocities gives input not only for autopilot, but also damping devices, such as yaw or pitch dampers for example. The MEMS (micro-electro-mechanical system) gyroscopes are much less reliable than their laser or fibre-optic cousins. Nevertheless, the availability and low price of MEMS components make this a growing area of application in avionics for general aviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Stochastic characteristics of sensors were also investigated using Allan variance [ 17 ] and generalized method of wavelet moments (GMWM) [ 12 , 26 ]. Figure 13 presents empirical wavelet variance (WV) of measured data (10 6 observations per parameter).…”
Section: Verification Of the Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Stochastic characteristics of sensors were also investigated using Allan variance [ 17 ] and generalized method of wavelet moments (GMWM) [ 12 , 26 ]. Figure 13 presents empirical wavelet variance (WV) of measured data (10 6 observations per parameter).…”
Section: Verification Of the Methodologymentioning
confidence: 99%
“…During one of the landings, the pilot unexpectedly experienced the shimmy vibrations of the front landing gear. The authors presented the analysis of this occurrence in detail in the 2017 paper [ 12 ]. One of the problems identified that required solution was the determination of the exact time of a touchdown by airframe vibrations analysis.…”
Section: The Idea Of a Touch-down Virtual Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the research tasks recently carried out by a team of researchers from the Department of Avionics and Control Systems, Rzeszów University of Technology, was to analyze the vibration and oscillation of an airplane using wavelet methods (Bakunowicz and Rzucidlo, 2017). Such analyses have also been carried out in other research centers but have applied to aircraft of other classes (Naruoka et al , 2009; Lichota et al , 2016).…”
Section: In-flight Experimentsmentioning
confidence: 99%